Epidemiology and Management for Health Care - Waingankar, Prasad (Indian Journal of Community Health, 2025)
Epidemiology and Management for Health Care by Sathe P. V. and Doke P. P. is an essential textbook that bridges the fields of epidemiology and healthcare management. The book aims to provide students, public health professionals, and healthcare administrators with a deep understanding of epidemiological principles and their applications in healthcare planning, decision-making, and policy implementation. Written in a clear and structured manner, it serves as a valuable resource for both academic and practical applications in the healthcare field. The 7th Edition of this textbook is published this year (2025) by Vora Medical Publication, Mumbai. When the first edition arrived in 1991, the distinctiveness of this book was immediately noticed and the book became popular as Dr. Sathe’s book among the post graduate students of Preventive & Social Medicine and medical officers in Public Health as it has correctly filled up the gap. Attention was paid up to the requirements of non-medical health and hospital administrators by the author who is former Director of Medical Education & Research, Maharashtra. There was no such guidance about the management principles and techniques in the health sector through lucid discussions easily available then. The fourth edition released in 2014 has seen much needed transition with joining of second author Dr Doke, former Director of Health Services, Maharashtra, which continued in successive editions. This seventh edition is successful in maintaining its uniqueness of giving anecdotes and real-life examples to illustrate the point under description making the book reading more interesting. The objective of this book is to briefly state the basics of epidemiology and management sciences and illustrate their application in the health field making the health care services more effective and efficient and health service provider more competent and assertive.